Re-Centring the City Global Mutations of Socialist Modernity - Bach, Jonathan; Murawski, Michał (Fringe, 2020)
What is the role of monumentality, verticality and centrality in the twenty-first century? Are palaces, skyscrapers and grand urban ensembles obsolete relics of twentieth-century modernity, inexorably giving way to a more humble and sustainable de-centred urban age? Or do the aesthetics and politics of pomp and grandiosity rather linger and even prosper in the cities of today and tomorrow? Re-Centring the City zooms in on these questions, taking as its point of departure the experience of Eurasian socialist cities, where twentieth-century high modernity arguably saw its most radical and furthest-reaching realisation. It frames the experience of global high modernity (and its unravelling) through the eyes of the socialist city, rather than the other way around: instead of explaining Warsaw or Moscow through the prism of Paris or New York, it refracts London, Mexico City and Chennai through the lens of Kyiv, Simferopol and the former Polish shtetls. This transdisciplinary volume re-centres the experiences of the 'Global East', and thereby our understanding of world urbanism, by shedding light on some of the still-extant (and often disavowed) forms of 'zombie' centrality, hierarchy and violence that pervade and shape our contemporary urban experience.